LA CRISIS ACTUAL DE LA SOCIOLOGÍA: DESVALORIZACIÓN SIMBÓLICA Y REVALORACIÓN ECONÓMICA - Uribe de Hincapié, Maria Teresa (La Sociología en sus Escenarios, 2010)
Abstract. Commentary of Professor Maria Teresa Uribe on the document of the reflection on the state of Sociology in Antioquia (1996). Professor Serna presents an ample glance, that gives account of the panorama of Sociology in Medellin, from the beginnings of this one in the shade of the social doctrine of the Church in the Pontifical University Bolivariana, to the somewhat eclectic times and to postmodern us of the present, happening through the gilded years of the seventy, in which a critical sociology was lived, but that somehow served as sustenance the political mobilization of the moment, as much in Medellin like other places of the country and Latin America. In the text of Alba Lucia Serna they announce, two thematic axes. The first thematic axis has to do with the declining identity of discipline that this losing its profiles and it would also be pronounced in the task of the sociologists who would have dedicated themselves to other labor fields or another type of activities, where its own professional task would be blurred. The second axis is an economic revaluation or of market, expressed not only in the increase of the demand of quotas in the universities, the increase of the demand of sociologists, that really is growing, and mainly a demand of sociologists who accompany social processes: of consultant’s offices, consultancies; elaboration of projects of intervention or administration, and workings of management of social programs very related with the state task or the one of the ONG - nongovernmental organizations In synthesis, is appraised a symbolic devaluation of the discipline and an economic revaluation and of market that would be plotting specific courses to him Sociology, by the end of the decade of the 90. Resumen. Comentario de la profesora María Teresa Uribe sobre el documento central de la Primera Jornada de Reflexión sobre el estado de la Sociología en Antioquia- 1996. La Profesora Serna presenta una mirada amplia y completa, que da cuenta del panorama de la Sociología en Medellín, desde los inicios de ésta a la sombra de la doctrina social de la Iglesia en la Universidad Pontificia Bolivariana, hasta los tiempos algo eclécticos y postmodernos del presente, pasando por los años dorados de los setenta, en los que se vivió una sociología crítica y más que crítica contestataria, pero que de alguna manera sirvió de sustento a la movilización política del momento, tanto en Medellín corno en otros lugares del país y de América Latina. En el texto de Alba Lucía Serna se anuncian, dos ejes temáticos. El primer eje temático tiene que ver con la declinante identidad de la disciplina ya que está perdiendo sus perfiles y ello se manifestaría también en el quehacer de los sociólogos que se habrían dedicado a otros campos laborales o a otro tipo de actividades, en donde su propio quehacer profesional estaría desdibujado. El segundo eje es una revalorización económica o de mercado, expresada no solamente en el incremento de la demanda de cupos en las universidades, en el aumento de la demanda de sociólogos, que realmente está creciendo, y sobre todo una demanda de sociólogos que acompañen procesos sociales: de asesorías, de consultorías; elaboración de proyectos de intervención o de administración, y labores de gestión de programas sociales muy ligados con el quehacer estatal o con el de las ONG -organizaciones no gubernamentales- En síntesis, se aprecia una desvalorización simbólica de la disciplina y una revalorización económica y de mercado que le estaría marcando unos rumbos específicos a la Sociología, a fines de década de los 90.